Meeting the Challenge of Cystic Fibrosis. Issue 1 (January 2015) - Callister, Lynn Clark
<x xml:space="preserve">Abstract</x> Life expectancy in those with Cystic Fibrosis varies widely, from 35-40 years in the United States and the United Kingdom to below 15 years in low resource countries including El Salvador, India, and Bulgaria. Globally, efforts are being made in an attempt to reduce morbidity and mortality associated with CF and increase public awareness of this birth defect.